1993
DOI: 10.1111/j.1399-3011.1993.tb00492.x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and stability of 3‐nitro‐2‐pyridinesulfenyl chloride (NpysCl)

Abstract: 3‐Nitro‐2‐pyridinesulfenyl chloride (NpysCl) is the starting material for the synthesis of N‐, O‐ and S‐Npys‐protected amino acids. Two efficient, novel synthetic routes to NpysCl are described. The stability of NpysCl was determined in a variety of solvents, with and without base, to determine the most suitable solvent and base for the synthesis of N‐Npys amino acids. The syntheses of Npys‐Ala and Boc‐Lys(Npys) tert‐butylammonium salt are also described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
0
9
2
Order By: Relevance
“…Finally, to demonstrate the usefulness of Npys‐OPh( p F) ( 1 ), we examined its stability, both during storage and in solution. In previous reports, the conventional protecting reagent Npys‐Cl was reported to be stable for several months at 4°C in a closed container . However, in our study, NMR analysis showed that 25% of Npys‐Cl was converted to the dimer after 3 weeks under these conditions.…”
Section: Resultscontrasting
confidence: 75%
See 4 more Smart Citations
“…Finally, to demonstrate the usefulness of Npys‐OPh( p F) ( 1 ), we examined its stability, both during storage and in solution. In previous reports, the conventional protecting reagent Npys‐Cl was reported to be stable for several months at 4°C in a closed container . However, in our study, NMR analysis showed that 25% of Npys‐Cl was converted to the dimer after 3 weeks under these conditions.…”
Section: Resultscontrasting
confidence: 75%
“…In previous reports, the conventional protecting reagent Npys-Cl was reported to be stable for several months at 4°C in a closed container. 11 However, in our study, NMR analysis showed that 25% of Npys-Cl was converted to the dimer after 3 weeks under these conditions. By contrast, no decomposition of our new reagent (1) was observed after 2 months at 4°C.…”
Section: Resultscontrasting
confidence: 65%
See 3 more Smart Citations